Rapid discontinuation of sodium channel–blocking antiseizure drugs evokes focal edema in the splenium corporis callosi: A matched case‐control study. (6th June 2019) - Zöllner, Johann Philipp; Rosenow, Felix; Wagner, Marlies; Hattingen, Elke; Müller‐Eschner, Monika; Strzelczyk, Adam
Abstract: Objective: Focal edema of the splenium of the corpus callosum (FESCC) is infrequently seen in patients with epilepsy who are undergoing video–electroencephalography (EEG) monitoring. It is diagnosed by qualitative visual inspection of the magnetic resonance imaging (MRI) and is usually assumed to be a dichotomous phenomenon. Rapid reduction of anticonvulsants has been proposed as a cause. In this study we investigate the relationship between dose reduction of anticonvulsants and the occurrence of FESCC, based on absolute drug doses. Methods: We examined in detail the anticonvulsive therapy of all patients during video‐EEG monitoring between 2014 and 2018. We compared patients with a radiologically diagnosed FESCC to controls in a 1:2 case‐control analysis matched by age, epilepsy syndrome, and adjacent time of admission. In a separate correlation analysis, we examined quantitative effects of reduction of antiseizure drugs on diffusion restriction in the corpus callosum. Results: Of 326 patients who had an MRI following video‐EEG monitoring, 12 (3.7%) had FESCC. Antiseizure drugs were reduced to a significantly greater extent in FESCC patients than in the 24 controls ( P < 0.001). Sodium channel–blocking antiseizure drugs were reduced ( P < 0.001) and reintroduced ( P < 0.001) significantly faster in FESCC patients, and the duration of anticonvulsant discontinuation was longer in FESCC patients ( P < 0.001). The separate correlation analysis in 325 patients shows a weak correlation between diffusion restriction in the splenium and the reduction rate of sodium channel–blocking anticonvulsants ( r = −0.15, P = 0.03) as well as the duration of their discontinuation ( r = −0.16, P = 0.01). No such effects were found for anticonvulsants with other modes of action. Significance: Our findings substantiate that FESCC is associated with high rates of dose reduction of anticonvulsants, specifically those acting on sodium channels. Our results cautiously suggest that reducing sodium‐channel blockers has a small effect on diffusivity in the splenium below the visual threshold.